Desain Pembelajaran Berbasis ICT untuk Pengembangan Desan Pembelajaran Berbasis Kompetensi (Competency Based Education) - Arifa Dina Hanifa; Laeli Dina Mafazah; Raida Sulistiya; Riris Eka Setiani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This article analyzes the urgency of integrating Information and Communication Technology (ICT) into the Competency-Based Education (CBE) framework as an innovative instructional design approach in the digital era. ICT integration emphasizes the use of technology to facilitate competency achievement through personalized, flexible, and learner-centered learning. This study employed a library research approach by reviewing relevant literature on ICT, CBE, and instructional design using the ADDIE model. The findings indicate that ICT implementation in CBE transforms teachers into facilitators and instructional designers, while students become active and independent learners. The model is characterized by broad access to digital learning resources, the use of Learning Management Systems (LMS), interactive learning media, and authentic competency-based assessment. The instructional design process follows the ADDIE stages of analysis, design, development, implementation, and evaluation to ensure alignment between learning activities and competency outcomes. Nevertheless, several challenges remain, including limited teachers' digital competencies, unequal access to technology, and the need for standardized digital competency-based assessment systems. Therefore, adequate infrastructure, continuous professional development, and adaptive educational policies are essential to optimize ICT integration in CBE and improve learning quality while fostering twenty-first-century skills.